Brand New Oldies: Recent English Narrative Verse - David Malcolm (Anglica. An International Journal of English Studies)
A substantial amount of narrative verse has been written and published in England in the first two decades of the 21st century. Several writers, including Bernardine Evaristo, Ros Barber, Patience Agbabi, and Moniza Alvi, have written successful and well-received longer narrative poems. These poems fall into various categories: novel in poems, verse novel, and narrative collection. Five features of these texts are distinguished: the reworking of traditional and popular story materials; the predominant deployment of traditional narrative and narrational technique; accessible verse technique; an interest in past subjects and an attempt to render them available to a contemporary readership; and an adoption of non-narrative and lyric modes.